Diabetes and cardiovascular diseases - Elgomaty, Nouralhuda Mohamed (faculty of Basic Medical Science - Libyan International Medical University, 2018)
Cardiovascular disease is a complication of Diabetes mellitus. diabetes is considered as a prime risk factor for CVD, also affects the heart muscle, causing both systolic and diastolic heart failure. When you have high blood glucose levels, this can contribute to the formation of fatty deposits in blood vessel walls. Over time, it can restrict blood flow and increase the risk of atherosclerosis, or hardening of the blood vessels In this report will discuss the relation between diabetes and cardiovascular disease
Cardiovascular disease is a major cause of death in Western countries, and it is becoming a major cause of death in developing countries. This increase may be due to the rising prevalence of many cardiovascular disease risk factors, such as diabetes.